Pengaruh LKS berorientasi concept attainment pada materi momentum, impuls dan getaran harmonis untuk meningkatkan pemahaman konsep fisika siswa SMA - Tria Sukma Sandi; festiyed festiyed; Yenni Darvina; Wahyuni Satria Dewi (Universitas Negeri Padang, 2019)
In learning the teacher still uses teaching materials that have not been able to train students to understand the concepts of physics, so understanding the concepts students have is still low. The use of Concept Attainment-oriented LKS is expected to be able to train students in understanding the concept of learning. So that the demands of the 2013 curriculum are reached, which requires students to play an active role in learning. This type of research is quasi-experimental research with the design of the Ramdomized Control Group Only Design without pretest. The population of this study was students of class X MIPA SMAN 2 Solok Selatan who were enrolled in the 2018/2019 Academic Year totaling 48 people. Sampling in this study using Cluster Random Sampling technique. The research instrument used was a written test essay instrument. The data in this study were analyzed using descriptive statistical analysis, two similarity tests on average, normality test, homogeneity test and hypothesis testing to determine the influence of research variables on the level of conceptual understanding. Based on the research carried out, it can be stated that the results of the study are the use of LKS with Concept Attainment in the material of momentum, impulses, and harmonious vibrations that give a significant difference to the understanding of students' concepts at the 5% level of error in class X MIPA SMAN 2 Solok Selatan. The use of Concept oriented LKS Attainment of momentum material, harmonious impulses and vibrations can improve students' understanding of concepts in school.